A confirmed bite by a Beautiful Pit Viper (Trimeresurus venustus) resulting in local symptoms. (May 2019) - Fuchs, Joan; Bessire, Karin; Weiler, Stefan
Abstract: This case report describes the effect of an envenomation by the Beautiful Pit Viper Trimeresurus venustus (or Cryptelytrops venustus ), which is a green pit viper native to Thailand and Malaysia. A previously healthy 60-year-old snake breeder with no relevant medical history was bitten by his adult T. venustus in the third finger of his right hand while taking it out of the feeding box. The bite was painful and swelling progressed to include his whole hand within an hour after the bite. He was treated symptomatically with pre-emptive antibiotics and analgesics, never developed any hematological disorders such as coagulopathy and bleeding or disseminated intravascular coagulation and was discharged 26 hours after the bite. The clinical course in our patient matched two other well-documented cases reported to our Poisons Centre, and one further case presented as a conference-poster. All patients recovered with symptomatic therapy and never required antivenom. Therefore, bites by T. venustus seem to present with less severe symptoms compared to other Trimeresurus species. Highlights: Describes human envenomation by the Beautiful Pit Viper, Trimeresurus venustus . Related species cause massive local symptoms and hematological disorders. The effects of the bite were local with moderate progression of swelling and pain. The patient experienced complete recovery within 26 hours.